A Proposed Training Program According To The Skills Of Knowledge Economy And Its Impact On Lateral Thinking Of Students Teachers And Their Trends Towards The Profession Of Teaching Mathematics - Jabbar Faris, Ilham; Risen Al-Kinani, Hassan Kamil; Jasim Al-Dulaimy, Basim Mahammad (Opción, 2019)
The present research aims to study the impact of an independent variable, the proposed training program that has been prepared according to the steps of preparing educational programs with special content, namely the skills of knowledge economy in its five fields. The proposed program was applied to a sample of students teachers who are students of the fourth stage in the Depart- ment of Mathematics. Those who are subjected to the program of practical education scheduled for fifteen weeks, the program was implemented for 7 weeks by 3 hours per week, including the theoretical side with workshops and video presentations and watch math lessons in schools where the education is carried out electronically. The experimental group led 46 students of the fourth stage students in the Department of Mathematics, and the same num- ber was the number of members of the control group and after the completion of the application of the program students were subjected to a test in later- al thinking and a measure of trends towards the profession of mathematics teaching have been specially prepared for this research according to the steps of preparing tests and standards The results indicated that the experimental research sample was superior to the control sample studied according to the usual program. Thus, the two hypotheses that were set to achieve the research objective were rejected.